Management Status of Myocarditis-Related Sudden Cardiac Death - Ping Yan; Shujun Yang; Tong Wang (Reviews in Cardiovascular Medicine)
Myocarditis, a life-threatening disease that can result in cardiac arrest and sudden cardiac death, has garnered significant attention in recent years. This review provides a comprehensive overview of the management of myocarditis-related sudden cardiac death, encompassing its pathology, diagnostic methods, therapeutic strategies, preventive measures, prognostic factors, and risk stratification. Additionally, the review highlights current challenges and future directions in this field. The aim is to enhance understanding of myocarditis-related sudden cardiac death and inform clinical practice, ultimately leading to improved patient outcomes.